Registro y traducción visual del personaje de “Colaguango” de la parroquia Belisario Quevedo a partir de testimonios, plasmados en cartillas infográficas - Chicaiza Rengifo, Grecia Verónica (2016)
The current investigation come up from the lack of knowledge of the “Fiscal de Colaguango” festivity, of the Belisario Quevedo Parish in Latacunga city, it is necessary because new generations don’t know about this ancestral and historical tradition. For this project we used some investigation methods, the first is the documental which is used to collect antecedents through formal an informal graphic methods which provide to the investigation the necessary fundation for the realization of this project, the second method used was the field research that is applied to obtain information in a direct way from the native place to know the different values and cultural wealth that this community own, the third method is bibliographic investigation which allows to collect all the information necessary to design the infographic cards to support the theoretical and scientific basis for a good development of the project, finally we used the descriptive investigation method which allows to know in a direct way all the information and characteristics of the “Fiscal de Colaguango”, its festivities, customs and tradition that were made by people in ancient times.